Trends in Survival for Classical Hodgkin Lymphoma (cHL) in the Modern Treatment Era: A SEER Population Study - Sorour, Selina; Abusada, Wala'a; Awamleh, Mohammed; Nabulsi, Abdelrahman (Asian Pacific Journal of Cancer Nursing, 2026)
Background: Classical Hodgkin lymphoma (cHL) is a highly curable malignancy. However, a subset of patients relapse or remain refractory to first-line therapy. Pembrolizumab, a PD-1 inhibitor, has shown favorable outcomes in clinical trials; this study assessed its impact on overall survival (OS) at the population level. Methods: We used data from the Surveillance, Epidemiology, and End Results (SEER) program. We included adults aged ≥20 years diagnosed with classical Hodgkin lymphoma from 2013 through 2021, excluding cases from 2017. Patients were divided into two groups: before pembrolizumab approval (2013–2016) and after approval (2018–2021). Overall survival (OS) was analyzed using Kaplan–Meier curves and log-rank tests. Multivariable Cox models were used to identify independent predictors of OS. Results: A total of 2,742 patients were included. Median overall survival was not reached in either cohort due to high survival rates and short follow-up time in the second period; therefore, restricted mean survival time at 60 months was used for comparison. The restricted mean OS was 57.0 months (95% CI: 56.5–57.6) in Period 1 and 56.4 months (95% CI: 55.8–57.0) in Period 2, with no significant difference between groups (χ²=0.490, p = 0.484). Multivariable Cox regression identified female sex (HR = 0.654, p = 0.003), younger age (p < 0.001), localized (HR = 0.637, p = 0.011) or regional disease (HR = 0.600, p = 0.003), lymphocyte-rich histology (HR = 0.338, p = 0.012) as factors associated with improved survival. Factors associated with increased mortality included not receiving chemotherapy (HR = 2.424, p < 0.001) or radiotherapy (HR = 2.205, p = 0.002). Time period was not associated with OS (p = 0.165). Conclusion: overall survival in cHL remained excellent and stable over time. While immune checkpoint inhibitors have transformed management of relapsed/refractory disease and offered potential improvements in survival, limitations in treatment-specific data and follow-up length emphasize the need for further research to fully understand the impact of new therapies.